FROM THE 1857 INTRODUCTION TO THE 1867 PREFACE: Reflections on Marx’s Method in the Critique of Political Economy - Jessop, Bob (Politeia, 2019)
Marx noted that beginning is difficult in all sciences. He was referring to the origins of classical political economy, his own road to the critique of the capital relation, and the challenges that readers might find in the opening chapters of Capital. His work on this text reflected the view of Marx and Engels that there was only one science: history, embracing nature and society. Unsurprisingly, then, the natural sciences shaped their work in important ways. My article notes the impact of Darwinism, thermodynamics and cell biology in Marx’s analyses and examines the least-discussed of these influences: cell biology. When Marx eventually settled on the value-form of the commodity as the starting point for his anatomy of civil society, he described it as the economic cell form of the capitalist mode of production. This analogy served an important heuristic function as he sought a starting point for his critique but he did not seek to translate it directly into his research process, let alone in his method of presentation. I then ask whether Marx’s account of the methods of political economy adumbrated in the 1857 Introduction adequately anticipate his method in Capital. It does not. His later interest in cell biology suggested another method and another way of applying Hegel’s Science of Logic. In this context, I identify six parallels between cell biology and Marx’s analysis of the capitalist mode of production and explore the heuristic and epistemological implications of beginning with the commodity as the elementary form of the capital relation. Nonetheless, these parallels affect the process of discovery more than the substantive focus of Marx’s research or the order of presentation, where Hegelian influences take a more prominent role. The contribution ends with some general conclusions on discovery, methods, and the method of presentation.
Keywords: starting point; natural sciences; money; method of research; method of presentation; commodity; cell theory; cell form; Capital